(untitled) (Heritage, 2022)
The purpose of this pilot study is to identify teachers’ attitudes to experimental forms of online teaching based on their initial three-month teaching experience gained during the academic year 2019/20, and provide deeper insights into the nature, management and quality of online teaching as alternate modality in all educational levels in Serbia and the Republic of Srpska. The conducted research involving 283 language and literature teachers was done by using the quantitative and qualitative method, and the survey questionnaire consisting of one open-ended and ten closed-ended questions was the measuring instrument.The responses are analyzed and classified into several categories according to their common denominator. The results shed light on major social, economic and psychological factors that affected the teachers’ attitudes to the nature, management and quality of online teaching as alternate modality to standard face-to-face instruction and highlighted the limitations of relying on face-to-face teaching as the only accessible delivery mode.